Achieving flexibility/rigidity balance through asymmetric Donor−Acceptor scaffolds in pursuit of dual state emission with application in acidochromism. (March 2021) - Singh, Vishwa Deepak; Kushwaha, Ashish Kumar; Singh, Roop Shikha
Abstract: Three novel chalcone based asymmetrical D–A–D′–A'chromophores (C1 –C3 ) have been designed and synthesized with intent to achieve dual state emission. It has been contemplated that introducing both flexible and rigid moieties to the D–A core will suffice for the emission in solution as well as solid state. In this regard flexible piperazine unit has been introduced along with rigid polyaromatic hydrocarbons anthracene, C1 ; pyrene, C2 and phenothiazine, C3 to afford an asymmetric D–A construct. The compounds have been thoroughly characterized by spectroscopic studies ( 1 H, 13 C, ESI–MS, UV/Vis and fluorescence). The compounds C1–C3 display varying degree of dual state emission as envisaged by photo-physical investigation in solution, aggregated and solid state along with quantum yield assessment. Notably the aggregation has been instigated in these compounds by taking advantage of relative hydrophilicity/hydrophobicity of different solvent systems. The revered intramolecular charge transfer (ICT) imparts substantial solvatochromism to these D−A constructs. The prudence of incorporation of heteroatomic phenothiazine unit to the designed chromophores is reflected in superior dual state emission and solvatochromism of C3. In addition, these compounds revealed remarkable acid–induced fluorescence quenching effect in solution and solid state as the emission of C1–C3 could be quenched by trifluoroacetic acid (TFA) significantly. Graphical abstract: Image 1